Dynamics of prooxidant-antioxidant system in patients with chronic hepatitis c with mixed cryoglobulinemia on a background of various schemes of pathogenetic treatment - O.P. Mashko; E.V. Ryabokon (Zaporozhye State Medical University, 2012)
Abstract It is shown that inclusion of immunomodulating remedy with antioxidant properties (erbisol) into the basic treatment in patients with chronic hepatitis C with mixed cryoglobulinemia can increase the effectiveness of pathogenetic treatment. Against the background of treatment by erbisol in these patients recovery of prooxidant-antioxidant balance and reduce of cytolytic syndrome severity are observed.